2008
DOI: 10.1097/mat.0b013e3181872d5b
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Neurophysiologic Monitoring on the Management of Pediatric Cardiopulmonary Bypass

Abstract: We describe a process by which we sought to determine how the addition of intraoperative neurophysiologic monitoring (IONM) impacted the management of cardiopulmonary bypass (CPB) during pediatric cardiac surgery. While maintaining a consistent team of surgeons, anesthesiologists, nurses, and perfusionists, a multi-modal, IONM program was established consisting of Near Infrared Spectroscopy, Transcranial Doppler, and eight channel electroencephalography. A retrospective review of cases from 1 year before the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…24,25 Moreover, the use of these technologies can add time and expense to the operation and may alter intraoperative management unnecessarily, potentially leading to unintended consequences, such as increased blood transfusion rates. 20 Although this initial study focused solely on a single neuromonitoring parameter (i.e., cerebral embolic signals), future studies should assess the correlation between late neurocognitive outcomes and other intraoperative monitoring parameters, such as near-infrared spectroscopy and electroencephalography. These subsequent studies may shed light on which technologies can provide the real-time data that is most predictive of late outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Moreover, the use of these technologies can add time and expense to the operation and may alter intraoperative management unnecessarily, potentially leading to unintended consequences, such as increased blood transfusion rates. 20 Although this initial study focused solely on a single neuromonitoring parameter (i.e., cerebral embolic signals), future studies should assess the correlation between late neurocognitive outcomes and other intraoperative monitoring parameters, such as near-infrared spectroscopy and electroencephalography. These subsequent studies may shed light on which technologies can provide the real-time data that is most predictive of late outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our multi-modality neuromonitoring protocol for pediatric cardiac surgery has been previously described. 20 Several surveillance technologies are routinely used, including near-infrared spectroscopy, transcranial Doppler ultrasound, electroencephalography and somatosensory-evoked potentials. This study focused specifically on cerebral embolic signals detected by transcranial Doppler.…”
Section: Methodsmentioning
confidence: 99%
“…Transfusion of red blood cells is among the several proposed interventions for perceived inadequate cerebral oxygen delivery based on neuromonitoring. Kimatian and colleagues 35 reported on the influence of the institution of a multimodality neuromonitoring strategy on transfusion rates at their institution. By comparing patient cohorts from time periods before and after the implementation of neuromonitoring, these authors found a significant increase in the amount of blood use at the initiation of cardiopulmonary bypass (ie, prime blood) as well as hematocrit levels at the conclusion of bypass prior to modified ultrafiltration.…”
Section: Multimodality Neuromonitoringmentioning
confidence: 99%